Urinary Excretion Rate of Antithrombin III Related Antigen in Cerebral Stroke - Matsuo, T; Shinomiya, K; Okuno, S; Matsuo, C; Matsuo, O (Thrombosis and Haemostasis, 1984)
The urinary excretion rate of antithrombin III related antigen (AT III RA) was examined in cerebral stroke. The excretion rate of AT III RA in cerebral hemorrhage (CH) was 12.33 ± 1.61 × 10-4 ml/min. The patients with CH were further classified into two groups: in group CH-I, whose consciousness state was stupor or further deteriorated including coma on admission, the excretion rate of AT III RA was 18.08 ± 2.50 × 10-4 ml/min. In group CH-II, whose consciousness state was clear on admission, the excretion rate of AT III RA was significantly lower than that in CH-I (6.20 ± 1.56 × 10-4 ml/min). The excretion rate in cerebral thrombosis (CT) was 1.96 ± 0.25 × 10-4 ml/min, which was significantly lower than that in CH. The excretion rate of AT III RA in both CH and CT was significantly higher than that in the healthy control group (0.29 ± 0.04 × 10-4 ml/min). Thus, AT III may change dynamically in cerebral stroke.
Keywords: Antithrombin III; Excretion rate; Cerebral stroke; Sandwich immunoassay